An Analysis of Participation in Decision Making Among Project Engineers - Ivancevich, John M. (Academy of Management Journal, 1979)
In this study the nine most relevant job decisions for project engineers were named by the engineers themselves. Five hypotheses focused on the degree of participation in decision making by the project engineers. The results indicate that, in a number of personality, affective, stress, and performance variables, the decisional ?deprived? and ?saturated? groups are different from the group in decisional ?equilibrium.?